Cervicalium: proposta de redesign do protetor cervical para motociclistas - Carvalho Filho, Idinei Francisco Pires de [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The number of motorcycle accidents has been increasing in recent years, as has the motorcycle fleet in Brazil. Rachimedullary trauma, know as (RMT) concerns, because most of Brazilian motorcyclists do not use other safety equipment for safe riding beyond the helmet, which serves only for cranioencephalic protection. Even though 94% of motorcyclists feel that only with helmet they are not fully protected, 18% do not have any other type of equipment. Few urban motorcyclists, 5%, worry about the integrity of the body's cervical region, which when compromised can lead to paraplegia, quadriplegia and death. The Brazilian motorcycle rider, who uses the motorcycle daily, is dissatisfied with the prices that are inaccessible to most, and the lack of practicality of the cervical protectors that are currently found on the market. The objective of this work is to present a proposal of redesign of the cervical protector for motorcyclists, based on the ergonomic recommendations applied in the region of the cervical spine. The proposal was based on a survey of scientific evidence through articles that analyze the Brazilian traffic, bibliographies in the area of product design and complementary studies on the cervical region biomechanics. The definition was presented through a virtual model, developed in a 3D modeling software, besides being based on the studies of ergonomic design methodology and design. For the redesign of the protector, it was sought to reduce the impact of the whiplash effect on the cervical, to improve the practicality when the user uses it before the piloting, and modify the production process and materials that attend the economic aspect of the project. These attributes aim to benefit the Brazilian motorcyclist in an increasingly violent traffic with motorcycles and with a society that needs practicality for all the activities carried out in the daily life

O número de acidentes de motociclistas vem aumentando nos últimos anos, assim como a frota de motocicletas no Brasil. Os traumatismos raquimedulares, conhecidos como TRM, preocupam, pois a maioria dos motociclistas brasileiros não usa outro tipo de equipamento de segurança para uma pilotagem segura além do capacete, este servindo apenas para a proteção cranioencefálica. Mesmo com 94% dos motociclistas acharem que apena com o capacete não estão protegidos integralmente, 18% não tem nenhum outro tipo de equipamento. Poucos dos motociclistas urbanos, 5%, se preocupam com a integridade da região cervical do corpo, que quando comprometida pode ocasionar paraplegia, tetraplegia e morte. O motociclista brasileiro, que usa a motocicleta cotidianamente está insatisfeito com os preços inacessíveis para a maioria, e com a falta de praticidade dos protetores cervicais atualmente encontrados no mercado. O objetivo deste trabalho é apresentar uma proposta de redesign do protetor cervical para motociclistas, fundamentado nas recomendações ergonômicas aplicadas na região da coluna cervical. A proposta foi fundamentada por um levantamento de evidências cientificas por meio de artigos que analisam o trânsito brasileiro, bibliografias na área de design de produto além de estudos complementares sobre a biomecânica da região cervical. A definição concebida foi apresentada através de um modelo virtual, desenvolvido em um software de modelagem 3D, além de ser fundamentado nos estudos da metodologia do design ergonômico e design. Para o redesign do protetor, buscou-se reduzir o impacto do efeito chicote na cervical, melhorar a praticidade quando o usuário for usá-lo antes da pilotagem, e modificar o processo de produção e materiais que atendessem o aspecto econômico do projeto. Tais atributos visam beneficiar o motociclista brasileiro em um trânsito cada vez mais violento com motos... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Motociclistas; Coluna cervical; Engenharia humana; Motorcyclists